2007
DOI: 10.1016/s0377-1237(07)80137-7
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomographic Findings in 50 Cases of Gall Bladder Carcinoma

Abstract: Original Article Introduction C arcinoma of the gall bladder (GB) is the fifth most common malignancy of the gastrointestinal tract and the commonest malignancy of the biliary tree [1,2]. It occurs primarily in the sixth to seventh decade of life and is four to five times more common in women [2,3]. Ultrasonography (USG) and computed tomography (CT) have revolutionized the diagnosis and management of carcinoma GB. Magnetic Resonance Imaging (MRI) is utilized only in inoperable cases with obstructive jaundice f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 10 publications
4
9
0
Order By: Relevance
“…cholelithiasis in 28 patients (57.1%), ascites and pleural effusion in 15 cases (30.6%) and peritoneal involvement was seen in 10 cases (20.4%). These findings in our study were comparable to the data reported by George et al (2007) in which infiltration into liver was seen in 36 (72%) cases, while infiltration into the adjacent structures such as duodenum, pancreas and omentum was seen in 23 (46%) cases at the time of diagnosis [14].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…cholelithiasis in 28 patients (57.1%), ascites and pleural effusion in 15 cases (30.6%) and peritoneal involvement was seen in 10 cases (20.4%). These findings in our study were comparable to the data reported by George et al (2007) in which infiltration into liver was seen in 36 (72%) cases, while infiltration into the adjacent structures such as duodenum, pancreas and omentum was seen in 23 (46%) cases at the time of diagnosis [14].…”
Section: Discussionsupporting
confidence: 91%
“…In the study conducted by George et al (2007) focal or diffuse wall thickening was appreciated in 12 (24%) cases and in our study the focal/diffuse wall thickening was observed in 16.3% cases [14].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…16 Gallbladder wall calcification and gall stones were observed in 8 cases (56%). The percentage of incidence of gall stones in our study was similar to the findings of Lt Col George et al who noted 50% incidence of gall stones in carcinoma gallbladder.…”
Section: Infiltrating Gallbladder Carcinomamentioning
confidence: 99%
“…Both GB wall calcification and gall stone are implicated as an aetiological factor in the pathogenesis of gallbladder carcinoma. 16 Kumar et al had described that liver is the most frequently involved organ by direct contiguous spread (65% of cases) followed by the colon (15%), duodenum (15%) and pancreas (6%). 17 In our study, most of the lesions were hypodense on plain study (100 %) and showed enhancement in arterial phase and portal venous phase which was predominantly peripheral in all the cases and no delayed phase enhancement was noted.…”
Section: Infiltrating Gallbladder Carcinomamentioning
confidence: 99%